A survey on the suitability of risk identification techniques in the current networked environment. (15th March 2021) - Aboutorab, Hamed; Hussain, Omar K.; Saberi, Morteza; Hussain, Farookh Khadeer; Chang, Elizabeth
Abstract: Risk management is a necessary consideration in any decision-making activity. In global supply chains that are increasingly becoming internetworked and data-centric, risk management assists risk managers in making smart decisions to achieve their desired outcomes. Because of its importance, there are many studies in the literature on supply chain risk management. However, most of these are from a managerial perspective, and very few provide a technical perspective by surveying the techniques that have been used for risk management and their effectiveness. In this paper, we focus on the activity of risk identification and assess the suitability of the techniques used for this process to be effective in the current networked supply chain environment. We do this by first surveying the domain-independent risk identification techniques proposed between 1980 and 2020 and study the type of technique they use, classifying them according to the proposed taxonomy and then evaluating them to determine whether they meet the requirements of identifying risks in the networked environment. We then survey the techniques used for supply chain risk identification between 1980 and 2020 and determine their suitability along with their limitations in meeting the requirements of identifying risks in the networked supply chain environment. Based on the identified gaps, we then present different solution considerations to inform supply chain risk managers of the improvements needed to be made in the process of risk identification to meet the requirements of networked global supply chains.